Os efeitos da transformação digital na cultura organizacional da atividade notarial: um estudo no contexto da Capital do Rio Grande do Sul - Manica, Inajara Patrícia (Universidade do Vale do Rio dos Sinos, 2022)
This current study aims to understand the impacts on organizational culture on notarial activity from the regulation of digital acts through Provision No. 100/2020 of the National Council of Justice. The changes that occurred in the activity under study were consequences of the Covid-19 pandemic. The sanitary restrictions forced the migration of the provision from face-to-face services to the hybrid model. The regulation has accelerated the digital transformation of the activity, which is still ongoing. The research covered the notary offices in Porto Alegre, Rio Grande do Sul, and the interviews were conducted with notaries and representatives. From the interviewees' experiences, the impacts on the studied context can be perceived. The research highlights the influences of digital transformation on organizational culture and its interrelationship with citizens, society and the State. The dissertation contributed valuable information to the notarial activity in Brazil, because it explored and analyzed a subject little studied in the academy about this segment, the effects of digital transformation in organizational culture. In this context, this research provides results and knowledge for organizations and academia.
Keywords: Atividade notarial; Provimento nº 100/2020; Cultura organizacional; Transformação digital; Notarial activity; Provision nº 100/2020; Organizational culture; Digital transformation; ACCNPQ::Ciências Sociais Aplicadas::Administração